2012
DOI: 10.1016/j.ijsp.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle screw instrumentation of thoracolumbar burst fractures: Biomechanical evaluation of screw configuration with pedicle screws at the level of the fracture

Abstract: BackgroundPosterior fixation alone may not be adequate to achieve and maintain burst fracture reduction. Adding screws in the fractured body may improve construct stiffness. This in vitro study evaluates the biomechanical effect of inserting pedicle screws in the fractured body compared with conventional short- and long-segment posterior fixation.MethodsStable and unstable L2 burst fractures were created in 8 calf spines (aged 18 weeks). Constructs were tested at 8 Nm in the intact state and then with instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…Since a study of pedicle screw fixation at fractured vertebrae was first reported in 1994, a series of biomechanical studies [811] also showed that pedicle screw fixation combined with screws at the fractured vertebrae could significantly improve the spinal stability and decrease the stress of pedicle screws in the upper and lower normal vertebrae. The similar advantages have also been reported for treatment of TL fractures, however, the evidence is mainly limited to low-quality observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since a study of pedicle screw fixation at fractured vertebrae was first reported in 1994, a series of biomechanical studies [811] also showed that pedicle screw fixation combined with screws at the fractured vertebrae could significantly improve the spinal stability and decrease the stress of pedicle screws in the upper and lower normal vertebrae. The similar advantages have also been reported for treatment of TL fractures, however, the evidence is mainly limited to low-quality observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Research has con rmed the bene cial therapeutic effect of short-segment posterior xation with pedicle screws in the injured vertebra as treatment for thoracolumbar fractures [6][7][8][9][10][11][12][13]. Biomechanically, the screws at the fracture level function as a push point with an anterior vector, creating a "lordorizing" force that restores the anterior vertebral height and corrects the kyphosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Inserting monoaxial or polyaxial pedicle screws at the level of vertebral fractures, as well as segmental xation of burst fractures, improves biomechanical stability. [6,7] In addition, several studies have shown that enhanced fracture-grade screws can improve the biomechanical stability of the construct [8][9][10][11], and some authors [7,12,13] have also suggested that pedicle screw xation combined with an intermediate screw in the fractured vertebra improves biomechanical stability with better reduction, less loss of correction, fewer instrument failures, and comparable or better clinical outcomes. However, it has not yet been ascertained whether inserting a monoaxial or polyaxial pedicle screw at a vertebral fracture yields better clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…This may be achieved by use of long-segment constructs, but this requires fusing of multiple motion segments and larger incisions, with an increased risk of complications. An alternative method is to include screws at the level of the fracture [21].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Guven et al [23] clinically showed increased stability and long-term maintenance with short same-segment fixation. Bolesta et al [21] documented that a short segment construct with pedicle screws at the fracture site showed equivalent biomechanical stability compared with a conventional long-segment construct in any of the loading conditions.…”
Section: Discussionmentioning
confidence: 99%